2008
DOI: 10.1093/jaoac/91.4.853
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Profile of a Wild Edible Mushroom (Suillus granulatus)

Abstract: Seventeen elements, Al, Ca, Cd, Co, Cr, Cu, Fe, K, Li, Mg, Mn, Na, Ni, P, Pb, V, and Zn (macroelements and trace elements) were investigated by Atomic Spectrometries on a particular wild edible mushroom collected in the central region of Argentina during 2 different years in the same season. The metal content profile in Suillus granulatus samples is given. The found quantities of Na, K, Ca, Mg, Fe, P, V, and Al were 0.40, 10.84, 0.48, 0.30, 0.57, 4.24, 0.18, and 1.23 g/kg dry weight, respectively. The levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A large amount of magnesium is found in M. procera (approximately 1500 mg/kg d.w.) [150], B. edulis (approximately 800 mg/kg d.w.) [151], and Suillus granulatus (approximately 300 mg/kg d.w.) [152]. It is worth noting that Dursun et al [153] determined a very high content of magnesium in M. esculenta, exceeding 4000 mg/kg d.w.…”
Section: Magnesiummentioning
confidence: 93%
“…A large amount of magnesium is found in M. procera (approximately 1500 mg/kg d.w.) [150], B. edulis (approximately 800 mg/kg d.w.) [151], and Suillus granulatus (approximately 300 mg/kg d.w.) [152]. It is worth noting that Dursun et al [153] determined a very high content of magnesium in M. esculenta, exceeding 4000 mg/kg d.w.…”
Section: Magnesiummentioning
confidence: 93%
“…Substitution of saturated fatty acids (SFAs) with monounsaturated fatty acids (MUFAs) leads to increased high density lipoprotein (HDL) cholesterol and decreased low-density lipoprotein (LDL) cholesterol, triacylglycerols, lipid oxidation and LDL susceptibility to oxidation [10]. The study of edible fungi in various parts of the world has included the analysis of the chemical composition and nutritional values as elements necessary to characterize and define other uses besides the gastronomic, as reported for wild mushrooms and cultivated in Spain [11], Italy [12], Portugal [13,14], Greece [15,16], Turkey [17], India [18], Iran [19], Thailand [20], Serbia [21], Brazil [22], Mexico [23] and Argentine [24,25,26]. In recent years, increased interest in human health, nutrition and disease prevention has enlarged consumer demand for functional foods [27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that heavy metal contents such as cadmium, lead, and arsenic in wild‐grown edible mushroom are higher than those in plants and fruits suggesting mushrooms possess an effective mechanism to take up heavy metals from the ecosystem and accumulate them in the fruit of bodies (Kalač and Svoboda 2000; Arce and others 2008). The nutritional values of trace elements, such as Fe, Zn, Mg, and Mn that play an essential role in biological processes are found at considerable higher contents in wild‐grown mushrooms, whereas nonessential elements, such as cadmium, lead, and arsenic are toxic in long exposure even in traces levels (Ouzouni and others 2009).…”
Section: Introductionmentioning
confidence: 99%